2019
DOI: 10.1051/ps/2018027
|View full text |Cite
|
Sign up to set email alerts
|

Rate optimal estimation of quadratic functionals in inverse problems with partially unknown operator and application to testing problems

Abstract: Synopsis. We consider the estimation of quadratic functionals in a Gaussian sequence model where the eigenvalues are supposed to be unknown and accessible through noisy observations only. Imposing smoothness assumptions both on the signal and the sequence of eigenvalues, we develop a minimax theory for this problem. We propose a truncated series estimator and show that it attains the optimal rate of convergence if the truncation parameter is chosen appropriately. Consequences for testing problems in inverse pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Johannes and Schwarz [JS13] and Marteu and Sapatinas [MS17], where the training data was supposed to consist of eigenfunctions of the operator T , whence the eigenvalues are observed with noise. In that setting, the different problem of estimating a quadratic functional was considered recently by Kroll [Kro19].…”
Section: Inverse Problems With Unknown Operatormentioning
confidence: 99%
“…Johannes and Schwarz [JS13] and Marteu and Sapatinas [MS17], where the training data was supposed to consist of eigenfunctions of the operator T , whence the eigenvalues are observed with noise. In that setting, the different problem of estimating a quadratic functional was considered recently by Kroll [Kro19].…”
Section: Inverse Problems With Unknown Operatormentioning
confidence: 99%
“…Let us note that by applying Markov's inequality, it can be shown that the test 1 T k > 0 with the simplified test statistic T k := q 2 k − q k (ω 2 q /v 2 q ) 2/α and k as in (2.9), also attains the minimax radius of testing ρ a q,v q (ε q ) ∨ ρ a q,v q (ϑ q σ q ). The approach of deriving radii of testing by applying Markov's inequality has for example been used in Kroll [2019]. Since we are in Section 3 also concerned with adaptive Bonferroni aggregation, we need the sharper bound given in Proposition 2.3 for the threshold constant in terms of α.…”
Section: Indirect Testing Proceduresmentioning
confidence: 99%
“…Restricting themselves to the goodness-of-fit (ϑq = 0q) testing task in the homoscedastic setting, Marteau and Sapatinas [2017] derive upper and lower bounds for the uniform radii, featuring a logarithmic gap. Treating the signal detection task and the goodness-of-fit testing task separately, Kroll [2019] establishes matching upper and lower bounds for the minimax radii of testing uniformly over null hypotheses in Θ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimax rate optimal estimation of a quadratic functional has also been analyzed in density deconvolutions and inverse regressions in Gaussian sequence models. See, for example, Butucea [2007], Butucea and Meziani [2011] and Kroll [2019]. As far as we know, there is no published work on minimax rate-optimal adaptive estimation of a quadratic functional in NPIV models yet.…”
Section: Introductionmentioning
confidence: 99%